The Impact of Kahoot to Enhance Students’ Participation and Reading Ability in ELT Classroom - Ary Ruchana, Hamidah; Rudi Hartono; Fahrur Rozi (English Education Journal, 2024)
This research investigated the impact of Kahoot on students' participation and reading ability in ELT classrooms. Conventional teaching methods were found to be ineffective, leading to low student engagement and poor reading scores. By incorporating Kahoot, the experimental group demonstrated significantly higher levels of participation and improved reading performance compared to the control group. These findings highlight the potential of Kahoot by applying a mixed-method type, quasi-experiment research design (quantitative research – t-test) and (qualitative research – observation and questionnaire). The results of the students’ participation in the control class were 2.33 with a low degree level. Whereas the results of students’ participation in the experimental class were 4.37 with a high degree level. Statistical test to determine whether there is an impact of using Kahoot on students’ participation and reading ability through an independent sample t-test using SPSS 25. As a result, Kahoot effectively enhances students' reading ability with a mean of  75.94. It means that the experimental class students' scores in reading ability are in a good category. The score of  Kahoot questionnaire in the experimental class with a mean of 4.61 with a high degree level. Kahoot is influential in improving students’ reading ability, hence it raises students’ grades.